Actividades de mantenimiento en la Edad del Bronce del sur peninsular: el cuidado y la socialización de individuos infantiles - Sánchez Romero, Margarita (Complutum, 2007)
In this paper we will analyse maintenance activities related to care and socialization of children during Bronze Age in the South of Iberian Peninsula. Our aim is in one hand to consider works and experiences derived from these practices and in the other hand an approach to children not only as objects but as actors in activities related to social organisation in these societies.